Ribât es-Salâm. Drammatica dell’ospitalità nell’opera teatrale Pierre e Mohamed di Adrien Candiard - Avenatti de Palumbo, Cecilia Inés (2024)
Fil: Avenatti de Palumbo, Cecilia Inés. Pontificia Universidad Católica Argentina; Argentina